Small-to-Medium-Scale Sensory Evaluation of Horticultural Crops: Standard Sensory Practices - Sean Michael Campbell; Charles A. Sims (EDIS)
This new 5-page publication of the UF/IFAS Environmental Horticulture Department is the third in a series designed to assist producers in the small-to-medium-sized sensory evaluation of their horticultural crops, summarizing the standard sensory evaluation practices established for testing environment, sample ballots, panelist recruitment, and sample preparation. Written by Sean M. Campbell and Charles A. Sims.